Governing healthcare in India: a policy capacity perspective. (June 2021) - Bali, Azad Singh; Ramesh, M.
After decades of neglect, in 2008, the Indian government launched a national health insurance programme to address the needs of the bulk of the population that could not afford healthcare. This was followed by the launch of another national programme in 2018 that further expanded insurance coverage. These schemes envision a large single-payer, insurance-based system covering about 110 million families. The central objective of this article is to assess the government's capacity to implement these ambitious programmes. We employ the policy capacity framework developed by Wu et al. to examine the types of capacities needed to achieve desired objectives in the health sector. The central argument of the article is that there are critical capacity deficits, especially along operational dimensions. Our conclusions are generalisable to other middle-income countries currently in the process of implementing similar prospective-payment health policy reforms. Points for practitioners: This article highlights the need for governments to prioritise the capacity for implementing health policy reforms. Efforts to achieve and sustain universal healthcare are contingent not only on appropriate policy design, mobilising required resources and building political support, but also on overcoming capacity deficits in implementation. The framework presented in this article serves as a useful tool for governments to diagnose strengths and weaknesses in the specific types of capacities (analytical, operational, and political) needed for universal health coverage.